Determination of 5-Fluorouracil in its Injection and Biological Fluid by Enhanced Chemiluminescence Based on Luminol-Ag(III) Complex Reaction in Alkaline Solution - Dong, Ya-Juan; Wang, Ting; Chen, Pei-Yun; Sun, Han-Wen (Asian Journal of Chemistry, 2015)
A novel chemiluminescence method was developed for the determination of 5-fluorouracil based on the chemiluminescence reaction between Ag(III) complex [Ag(HIO6)2]5- and luminol in alkaline solution. Chemiluminescence emission of [Ag(HIO6)2]5--luminol in alkaline medium was different from that in acidic medium. A possible mechanism of enhanced chemiluminescence emission was suggested. The enhanced effect of 5-fluorouracil on chemiluminescence emission of the [Ag(HIO6)2]5--luminol system was found. The effect of the reaction conditions on chemiluminescence emission was examined and optimized. The chemiluminescence intensity was proportional to the logarithm of 5-fluorouracil concentration with correlation coefficient (r) of 0.9954 in the range of 10-5000 ng/mL. Under the optimized conditions, the limit of detection (LOD) was 3 ng/mL. The chemiluminescence system was applied for the determination of 5-fluorouracil in its injection and biological fluid with the recoveries of 94.6-104 % and with the RSD of 1.2-2.8 %. The proposed flow-injection chemiluminescence method provides high sensitivity necessary for analysis of 5-fluorouracil in pharmaceutical and biological fluids at clinically relevant concentrations.